1991
DOI: 10.1001/jama.1991.03470190078033
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Skin Tanning by Subcutaneous Administration of a Potent Synthetic Melanotropin

Abstract: -A significant parabolic curve of skin darkening activity was noted in subjects with skin type I or II (P less than .001) and with skin type III or IV (P much less than .001) who were given NDP. No darkening occurred in the subjects who were given a placebo. Peak changes were seen 1 to 3 weeks after therapy was completed. CONCLUSION--Human skin darkens as a response to a synthetic melanotropin given by subcutaneous injection. Skin tanning appears possible without potentially harmful exposure to ultraviolet rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 21 publications
2
69
1
Order By: Relevance
“…For many years, there has been a wide interest in developing melanocortin analogs that can be used for "sunless tanning", to avoid the deleterious effects of UVR. Although analogs of ␣-MSH with potent pigmentary effects have been developed (27,28), yet they were not efficacious as tanning agents due to their inability to be delivered topically due to their size, and their nonselectivity for the MC1R. In this study, we have tested on cultured human melanocytes the effects of 2 N-capped tetrapeptide analogs of ␣-MSH (2 and 3) and compared them to those of the tetrapeptide Ac-His-D-Phe-Arg-Trp-NH 2 (1) and the native hormone ␣-MSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, there has been a wide interest in developing melanocortin analogs that can be used for "sunless tanning", to avoid the deleterious effects of UVR. Although analogs of ␣-MSH with potent pigmentary effects have been developed (27,28), yet they were not efficacious as tanning agents due to their inability to be delivered topically due to their size, and their nonselectivity for the MC1R. In this study, we have tested on cultured human melanocytes the effects of 2 N-capped tetrapeptide analogs of ␣-MSH (2 and 3) and compared them to those of the tetrapeptide Ac-His-D-Phe-Arg-Trp-NH 2 (1) and the native hormone ␣-MSH.…”
Section: Discussionmentioning
confidence: 99%
“…A melanocortin analog intended for topical use is expected to mimic the effects of ␣-MSH on human melanocytes, have potent and reversible effects, and to be selective for the MC1R. These requirements should be fulfilled in order to avoid other nonpigmentary effects of melanocortins that result from activating the four other melanocortin receptors (MC2-MC5 R; 32), as observed in subjects injected with NDP-MSH (27). It was reported that increasing the number of N-terminal capping group methylene units results in increased selectivity for the MC1R vs. MC3R or MC4R (17).…”
Section: Figurementioning
confidence: 99%
“…Melanocytes are neuronal in origin and they synthesize the pigment melanin in response to physical stimuli such as ultraviolet (UV) radiation or to hormones such as a-melanocyte stimulating hormone (a-MSH). Stimulation of the melanocortin 1 receptor by a-MSH stimulates cAMP production (as do agents such as forskolin and cholera toxin) and this induces melanocyte differentiation in vitro and in vivo [95,96]. In the skin, melanocytes are thought to divide very rarely, but they can be induced to proliferate in culture if provided with a complex set of signals including those from receptor and nonreceptor tyrosine kinases, PKC and -unexpectedly -the cAMP pathway.…”
Section: Melanocytes/melanomamentioning
confidence: 99%
“…However, some data suggest that such signals may involve a local paracrine loop occurring in the context of immediate contact between melanocytes and keratinocytes. In vivo, melanogenesis is stimulated by ultraviolet (UV) radiation (8) and by α-melanocyte-stimulating hormone (MSH) (9). In vitro, the melanogenic effects of UV radiation and of MSH can be mimicked by pharmacological agents such as forskolin, cholera toxin, and isobutylmethylxanthine.…”
mentioning
confidence: 99%